Implications of the Venezuelan Migration Crisis for the Brazilian Security and Defense Policy: Perspectives for Conflict Management - Nogara, Tiago Soares (2019)
This article has the aim of identifying the main implications of the current Venezuelan migratory crisis for the formulation of Brazilian security and defense policy. Our hypothesis is that the exponential increase in the migratory flow of Venezuelans into Brazilian territory has serious geopolitical implications which are absent in public debate due to a false dichotomy contrasting security and humanitarian dimensions of migration. In this context, diplomatic action in the mediation of Venezuelan political confrontation and the role of the national State in the reception and regularization of Venezuelan immigrants appear as measures related to Brazilian strategic interests meant to avoid the overflow of the conflict beyond the borders of Venezuela so guaranteeing national sovereignty in issues related to increased migration flows.